2009
DOI: 10.1002/chem.200901557
|View full text |Cite
|
Sign up to set email alerts
|

A Gold‐Catalyzed Cascade Reaction Involving an Unusual Intramolecular Redox Process

Abstract: This study focuses on the effect of projected changes in rainfall, snow accumulation and snowmelt, and consequent changes in the timing of runoff on NYC water supply system storage and operation as simulated by the NYC reservoir system Operational Analysis and Simulation of Integrated Systems (OASIS) model. The Generalized Watershed Loading Functions—Variable Source Area (GWLF‐VSA)—watershed model is used with future climate scenarios derived from different General Circulation Models (GCMs) to simulate future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…[10] In fact, we found that the reaction proceeded in the presence of 5 mol % of AgOTf. Our experience in cycloisomerization reactions indicated that our desired transformation could be catalyzed by a metallic complex derived from typical carbophilic Lewis acids.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…[10] In fact, we found that the reaction proceeded in the presence of 5 mol % of AgOTf. Our experience in cycloisomerization reactions indicated that our desired transformation could be catalyzed by a metallic complex derived from typical carbophilic Lewis acids.…”
mentioning
confidence: 89%
“…Our experience in cycloisomerization reactions indicated that our desired transformation could be catalyzed by a metallic complex derived from typical carbophilic Lewis acids. [10] In fact, we found that the reaction proceeded in the presence of 5 mol % of AgOTf. To avoid possible decomposition of compound 4 as a result of the presence of the new reactive pyran ring, we directly performed the hydrogenation of the carbon-carbon double bond of this pyran ring under conventional conditions (Scheme 3).…”
mentioning
confidence: 99%
“…In a 2009 study, Barluenga and co‐workers observed that the Au + ‐catalyzed addition of indole 168 to alkyne 169 was accompanied by an internal redox isomerization to form saturated ketone 170 (Scheme ) 68. This process was generalized to include substituted indole, pyrrole, and various alkynol substrates forming the desired products in excellent yields.…”
Section: Ch Functionalization By Intramolecular Hydride Transfermentioning
confidence: 99%
“…This field has matured into well-established applications in organic synthesis. [2][3][4][5][6] For example, treating vinyl or aryl-substituted alkoxy carbenes with alkynes yields phenols and naphthols, respectively (Scheme 1a, Dötz benzannulation reaction). [7][8][9][10][11][12][13] Carbenes with 1,3-difluorphenyl-, cyclopropyl or ferrocenyl substituents furnish cyclobutenones (or cyclopentenones) in the presence of alkynes (Scheme 1a, Zora).…”
Section: Introductionmentioning
confidence: 99%